2008
DOI: 10.1536/ihj.49.221
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 Receptor-Mediated Ca2+ Signaling and Spontaneous Ca2+ Releases in Human Valvular Myofibroblasts

Abstract: SUMMARY (Int Heart J 2008; 49: 221-236)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Another possible approach to assess the degree and type of intercellular coupling is to analyse Ca [i] oscillations with a frequency comparable with our observations (10-30 mHz), have been reported in fibroblastic cells only in response to various stimuli (Corps et al, 1989;Diliberto et al, 1994;Harootunian et al, 1991;Liang et al, 2003;Ridefelt et al, 1995;Uhlen et al, 2006;Wu et al, 2004). Our experiments establish for the first time that both cultured fibroblasts and myofibroblasts exhibit spontaneous and highly periodic Ca 2+ [i] oscillations, which occur with higher frequency in myofibroblasts.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another possible approach to assess the degree and type of intercellular coupling is to analyse Ca [i] oscillations with a frequency comparable with our observations (10-30 mHz), have been reported in fibroblastic cells only in response to various stimuli (Corps et al, 1989;Diliberto et al, 1994;Harootunian et al, 1991;Liang et al, 2003;Ridefelt et al, 1995;Uhlen et al, 2006;Wu et al, 2004). Our experiments establish for the first time that both cultured fibroblasts and myofibroblasts exhibit spontaneous and highly periodic Ca 2+ [i] oscillations, which occur with higher frequency in myofibroblasts.…”
Section: Discussionsupporting
confidence: 84%
“…[i] oscillations have been described in different fibroblasts in response to various stimuli (Corps et al, 1989;Diliberto et al, 1994;Harootunian et al, 1991;Liang et al, 2003;Ridefelt et al, 1995;Uhlen et al, 2006;Wu et al, 2004) …”
Section: +mentioning
confidence: 99%
“…For certain experiments, valvular interstitial cells were used that had been isolated from noncalcified aortic valve leaflets (collected by the Cardiovascular Pathology Registry, St. Paul's Hospital, Vancouver, Canada) by enzymatic digestion, as we have previously described [28][29][30]. The valve leaflets were taken under ethics protocol from the explanted heart at the time of cardiac transplantation from a 47-yearold male patient with no history of heart valve disease.…”
Section: Cell Culturementioning
confidence: 99%
“…In fibroblastic cells, single [Ca 2+ ] i increases lead to contractile responses within tens of seconds after chemical and mechanical stimulation (Follonier et al, 2008;Munevar et al, 2004 ] i oscillations with comparable frequencies have been reported to occur in different cultured fibroblasts after various stimuli (Arora et al, 1994;Chen et al, 2010;Diliberto et al, 1994;Harootunian et al, 1991;Liang et al, 2003;Ridefelt et al, 1995;Uhlen et al, 2006;Wu et al, 2004); however, cell contractile events were not assessed in these studies. Rhythmic cortical pulsations were described for fibroblasts in suspension (Salbreux et al, 2007) and for spreading fibroblasts after microtubule depolymerisation -in the latter case, preceded by [Ca 2+ ] i transients (Pletjushkina et al, 1756 Journal of Cell Science 123 (10) 2001).…”
mentioning
confidence: 90%